Know-how y RR. PP en el desarrollo comunicacional empresarial - Unamuno Rojas, Keyla Angelica (2024)
The objective of this research is the development of Know-How and HR. PP in business communication development, taking as a reference the importance that this topic has in the field of strategic communication and institutional branding. The approach applied is of a mixed or dual order, which presents quantitative and qualitative elements, the level of the research is of an exploratory and descriptive order since it seeks to relate and deepen the importance of the processes or schemes that organizational communication must maintain in the face of these . processes, taking as a reference the object of study or case that will be the service company Biomedik S.A, the collection techniques applied were the interview with the target groups or prosumers of Biomedik services, observation sheet regarding the service and projection that the institution has with its work groups that project through its publications and corporate structure. As a result, it seeks to characterize the structure of communication as a proposal or projection in the face of the development of Public Relations and its integrative processes that it has in relation to the image, reputation and line of work by the institutions that apply, of the same forms its interaction that generates a relationship between service and satisfaction of its stakeholders and potential clients.